Asas Penyelenggaraan Sistem Jaminan Sosial Nasional Oleh Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan di Kota Jambi - Pahlefi Pahlefi; Nelli Herlina; Herlina Manik (Wajah Hukum, 2021)
This article is the result of research with the aim of analyzing and examining the principles in the implementation of the National Social Security System by BPJS Kesehatan in Jambi City. Then it aims to study and analyze the problems and efforts to overcome the problems. The research carried out is a type of empirical research, which concentrates on the main data from the field. The sampling method is through the 'accidental sampling' technique. The result of the research states that the humanitarian principle and the principle of benefit have mostly been implemented in BPJS services at the Hospital in Jambi City. Only the principle of social justice for all Indonesian people is still obscured and its implementation has not yet been seen in the implementation of health services by BPJS at Jambi City Hospital. Furthermore, there are still problems in the implementation of the BPJS in Jambi City, namely some of the losses in the implementation of the National Health Insurance, the unfairness of claims by participants in certain groups, unequal facilities and health workers in Hospitals.